Online Internal Temperature Sensors in Lithium-Ion Batteries: State-of-the-Art and Future Trends - Jinasena , Asanthi; Spitthoff , Lena; Wahl , Markus Solberg; Lamb , Jacob Joseph; Shearing , Paul R.; Strømman , Anders Hammer; Burheim , Odne Stokke (Frontiers in Chemical Engineering, 2022)
The temperature of the lithium-ion battery is a crucial measurement during usage for better operation, safety and health of the battery. In-situ monitoring of the internal temperature of the cells is an important input for temperature control of battery management systems and various other related measurements of the battery, such as state-of-charge and state-of-health. Currently, most commercial battery management systems rely on the surface temperature measurements of the cell. However, the internal temperature is comparatively higher than the surface temperature due to heat generation within the cell and lower heat rejection compared to the surface; therefore, accurate internal temperature monitoring methods are essential to improve our knowledge of battery safety and health. This paper reviews the most recent studies of various online internal temperature monitoring techniques under two main themes of hard sensors and soft sensors. The hard sensors include sensors that need to be inserted into the cell and other methods that use contact-less measuring techniques to infer the internal temperature. The soft sensors include estimators/observers that use surface measurements and various models to estimate the internal temperature. More focus is given to the soft sensors due to the lack of an existing, in-depth review of these. These methods are analyzed in detail with their accuracy, implementation, measurement frequency, and the common challenges and benefits are discussed. Further, possible future trends in internal temperature sensing are also discussed.